Multidrug-resistant Cutibacterium avidum isolated from patients with acne vulgaris and other infections. (March 2022) - Koizumi, Juri; Nakase, Keisuke; Hayashi, Nobukazu; Nasu, Yutaka; Hirai, Yuji; Nakaminami, Hidemasa
Highlights: Macrolide-, clindamycin- and quinolone-resistant C. avidum isolates from patients with acne vulgaris and other infections. erm (X) conferring macrolide–clindamycin resistance was prevalent in clarithromycin/clindamycin-resistant C. avidum strains. Antimicrobial use for treatment of acne vulgaris may be related to the development of antimicrobial-resistant strains. ABSTRACT: Objectives: Cutibacterium avidum, a human skin commensal bacterium, rarely causes infections. It has recently been shown that Cutibacterium acnes, another member of the genus, acts as an opportunistic pathogen in surgical site infections. However, the antimicrobial susceptibility and pathogenicity of C. avidum remain unknown. Methods: We investigated the epidemiological features and antimicrobial susceptibility of C. avidum isolated from patients with acne vulgaris and other infections. Results: Cutibacterium avidum strains were isolated from patients with acne vulgaris (29 strains) and other infections (12 strains). Clarithromycin and clindamycin resistance was observed in 65.9% (27/41) of strains. In addition, ciprofloxacin resistance was observed in 34.1% (14/41) of strains, of which 13 also exhibited resistance to macrolides and clindamycin. Notably, the macrolide–clindamycin resistance gene erm (X) was found on the chromosome of 92.6% (25/27) of clindamycin-resistant strains and may be prevalent owing to transmission among C. avidum strains. Ciprofloxacin-resistant strains developed amino acid substitutions in GyrA owing to the use of antimicrobial agents. Pulsed-field gel electrophoresis (PFGE) analysis revealed that only a few strains exhibited 100% similarity. Additionally, no clustering associated with antimicrobial resistance, biofilm-forming ability or type of infection was observed. Conclusion: Our study revealed that erm (X) may be frequently disseminated in C. avidum, and multidrug-resistant C. avidum strains may colonise the skin of patients with acne vulgaris and other infections. Therefore, the prevalence of multidrug-resistant C. avidum and the use of antimicrobial agents for the treatment of acne vulgaris and other infections associated with C. avidum should be monitored.